Implementation of Birth Certificate Preparation for a Mother's Child through Klampid New Generation (KNG) in Rungkut Menanggal Village - Zakiyah, Nuruz; Diana Hertati (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2024)
Public services can be defined as all forms of services carried out by service providers with the aim of meeting community needs. Kelurahan as one of the public service providers closest to the community has various forms of services, one of which is the embassy of birth certificates. One type of birth certificate is the birth certificate of a mother's child which is specially made because the parents of the child only have a siri marriage or are pregnant outside of marriage. In Rungkut Menanggal village, the processing of a mother's child birth certificate document is also the same as the processing of a child birth certificate in general, which uses the Klampid New Generation (KNG) innovation. The existence of KNG makes service easy because it is very effective and efficient compared to the past. This research uses descriptive qualitative methods. The theory used is Surabaya Mayor Regulation Number 10 of 2022 concerning procedures for implementing population administration. The results of this study indicate that the service of making a mother's child birth certificate at the Rungkut Menanggal Village Office can be said to be good, because 5 aspects of public service have been fulfilled, namely time efficiency, simplicity, security, attitudes and responsibilities of officers, and facilities and infrastructure.